COVID-19 ambassadors: Recognizing Kampus Mengajar at the Merdeka Belajar Kampus Merdeka program humanitarian projects in the tertiary education curriculum - Suyadi,; Wahyu Asmorojati, Anom; Yudhana, Anton; Nuryana, Zalik; Binti Siraj, Saedah (Frontiers in Education, 2022)
As of April 2022, various countries around the world have shown their success in tackling the COVID-19 pandemic, including Indonesia. One of the COVID-19 mitigation policies in Indonesia is the involvement of students as COVID-19 ambassadors through a program called Campus Teaching which carries 12 credits. However, the COVID-19 ambassador experienced academic injustice because the participating study programs and faculties did not recognize the program. The purpose of this research is to analyze the recognition of COVID-19 ambassadors who participate in the program. This research uses a case study type of qualitative research. The research setting is Universitas Ahmad Dahlan involving seventy students of the program and seven heads of faculties and study programs. Observation and in-depth interviews were administered with the head of the faculty and study programs. The results showed that study programs and faculties at universities could only recognize the activities of COVID-19 ambassador students in the program that have relevance to certain subjects. Thus, the higher education unit bureaucracy has lost its human dimension and is unfair to the student ambassadors of COVID-19. The implications of the findings of this study become a scathing critique of the fading of human values in higher education.